FORMATION OF ONE DIMENSIONAL ELECTRON CHANNEL NEAR THE ABRUPT INTERFACE OF TWO QUANTUM-SIZE FILMS WITH DIFFERENT THICKNESS - Yesayan, A. E. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
The confinement potential and charge distribution in the abrupt contact of two two-dimensional systems is considered theoretically. It is shown that a quasi- one dimensional electron channel can be formed near the interface between two quantum-size semiconductor films with different thickness and doping levels. Using the structure with double such “dimensional” heterojunctions a rectangular potential well confining one-dimensional electrons (quantum wire) can be realized.
Keywords: two-dimensional systems; confinement potential; electron channel; quantum-size semiconductor